EXATIDÃO DE MÉTODOS PARA ESTIMATIVA DO VOLUME DE ÁRVORES EM PÉ EM SISTEMA DE INTEGRAÇÃO LAVOURA-PECUÁRIA-FLORESTA - CURTO, Rafaella De Angeli; PINTO, Mônica Ferreira; ARAÚJO, Emanuel José Gomes de; WINK, Charlote; TONINI, Helio; LAURO, Aline Cristina (Brazilian Journal of Biometrics, 2019)
The aim of this study was to verify the accuracy of methods for estimating the total volume of standing trees in crop-livestock-forest production systems. The study was carried out in crop-livestock-forest production system, cultivated with Eucalyptus grandis × Eucalyptus urophylla (clone H13), at EMBRAPA Agrossilvipastoril, in Sinop, Mato Grosso, Brazil. Twenty trees were selected, in which the total individual volume was estimated by the methods of Pressler, Hossfeld, form factor and cubed with Criterion RD 1000® dendrometer and the actual total volume with the tree felled, the latter two by the Smalian method. The methods were compared by T-test, with 95% probability, residue analysis and accuracy. The results indicated that the Pressler and Hossfeld methods provide estimates tending to overestimate and underestimate, respectively, the total volume of trees. The total volume estimated using Criterion RD 1000® is more accurate among the methods tested for estimating the volume of standing trees. However, the high cost of this device may make its use impractical. The estimation of the total volume using form factor allowed to quantify the wood stock with accuracy, being feasible.